Tailored Exercise and Home Hazard Reduction Program for Fall Prevention in Older People With Cognitive Impairment: The i-FOCIS Randomized Controlled Trial. (19th September 2020) - Taylor, Morag E; Wesson, Jacqueline; Sherrington, Catherine; Hill, Keith D; Kurrle, Susan; Lord, Stephen R; Brodaty, Henry; Howard, Kirsten; O'Rourke, Sandra D; Clemson, Lindy; Payne, Narelle; Toson, Barbara; et al.
Abstract: Background: The evidence to support effective fall prevention strategies in older people with cognitive impairment (CI) is limited. The aim of this randomized controlled trial (RCT) was to determine the efficacy of a fall prevention intervention in older people with CI. Method: RCT involving 309 community-dwelling older people with CI. The intervention group ( n = 153) received an individually prescribed home hazard reduction and home-based exercise program during the 12-month study period. The control group ( n = 156) received usual care. The primary outcome was rate of falls. Secondary outcomes included faller/multiple faller status, physical function, and quality of life. Results: Participants' average age was 82 years (95% CI 82–83) and 49% were female. There was no significant difference in the rate of falls (incidence rate ratio [IRR] 1.05; 95% confidence interval [95% CI] 0.73–1.51). A sensitivity analysis, controlling for baseline differences and capping the number of falls at 12 (4 participants), revealed a nonsignificant reduction in fall rate in the intervention group (IRR 0.78; 95% CI 0.57–1.07). Analyses of secondary outcomes indicated the intervention significantly reduced the number of multiple fallers by 26% (RR 0.74; 95% CI 0.54–0.99) when adjusting for baseline differences. There was a differential impact on falls in relation to physical function (interaction term p -value = .023) with a significant reduction in fall rate in intervention group participants with better baseline physical function (IRR 0.60; 95% CI 0.37–0.98). There were no significant between-group differences for other secondary outcomes. Conclusions: This intervention did not significantly reduce the fall rate in community-dwelling older people with CI. The intervention did reduce the fall rate in participants with better baseline physical function. Clinical Trials Registration Number: Australian and New Zealand Trials Registry ACTRN12614000603617.